Analisis Etika Periklanan dan Dampak Sosial Iklan Sabun Mandi Lifebuoy “5 Tahun Bisa untuk NTT” pada Desa Bitobe, Nusa Tenggara Timur, Tahun 2023 - Syaiful Abdy; Reidhia Salsabila; Fitalia Bunga; Daniel Handoko (SABER : Jurnal Teknik Informatika, Sains dan Ilmu Komunikasi, 2024)
This study examines the advertising ethics and social impact of Lifebuoy soap advertisement with the theme "5 Tahun Bisa untuk NTT" (5 Years for NTT), aired in Bitobe Village, East Nusa Tenggara in 2023. Bitobe Village was chosen due to its representation of the typical socio-economic conditions in East Nusa Tenggara, often facing challenges related to sanitation and health. The research aims to analyze how the advertisement message is understood and received by the local community, as well as the implications of this message on hygiene-related behaviors and attitudes. The methods employed include content analysis of the advertisement and a social impact study through interviews and direct observations with the residents of Bitobe Village. The findings are expected to provide deeper insights into advertising ethics practices in a local context and their contribution to social change in marginalized communities.